2017
DOI: 10.1097/md.0000000000008512
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte and aspartate-to-alanine aminotransferase ratios predict hepatocellular carcinoma prognosis after transarterial embolization

Abstract: The neutrophil-to-lymphocyte ratio (NLR) reflects the systematic inflammatory status, and the aspartate aminotransferase-to-alanine aminotransferase ratio (AAR) is a biomarker of liver fibrosis and cirrhosis. These values can be conveniently obtained from routine blood tests; however, their combined clinical utility has not been extensively studied in patients with hepatocellular carcinoma (HCC) undergoing transarterial chemoembolization (TACE). This study aimed to investigate the prognostic value of NLR-AAR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 27 publications
(28 reference statements)
2
29
0
Order By: Relevance
“…However, CRP and ALP were both excluded after the multivariate analysis, indicating that the NLR–PLR score was a more powerful predictor than CRP and ALP and was representative as an inflammation-based prognostic factor in patients with HCC, compared with other inflammation-based factors. There were some previous studies which focused on inflammation-based factors,58,59 such as NLR and PLR in HCC patients after TACE therapy, while they only discussed the prognostic effect of a single factor. Similarly, in our study, the Kaplan–Meier analysis showed that elevated NLR or PLR was associated with poor OS, these parameters were suboptimal for predicting OS.…”
Section: Discussionmentioning
confidence: 99%
“…However, CRP and ALP were both excluded after the multivariate analysis, indicating that the NLR–PLR score was a more powerful predictor than CRP and ALP and was representative as an inflammation-based prognostic factor in patients with HCC, compared with other inflammation-based factors. There were some previous studies which focused on inflammation-based factors,58,59 such as NLR and PLR in HCC patients after TACE therapy, while they only discussed the prognostic effect of a single factor. Similarly, in our study, the Kaplan–Meier analysis showed that elevated NLR or PLR was associated with poor OS, these parameters were suboptimal for predicting OS.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 22 studies [2,5,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] published between 2011 and 2019 were identified and all these trials were retrospective cohort studies with 5280 patients enrolled in this meta-analysis. The basic characteristics of the included studies were summarized and presented in Table 1.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Sample sizes ranged from 49 to 921. Of the 22 studies, 16 of studies [2,5,19,21,[23][24][25][27][28][29][30][31][32][33][34]37] were about the prognostic value of preoperative NLR for OS, 5 about PLR [23,24,26,32,33] and 6 about CRP [20,22,33,35,36,38]. The NLR cut-off values in these studies were determined by different methods and ranged from 1.77 to 5.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…For quality assessment of included study, baseline data of these studies were extracted and exhibited in Table 1. Regions of these 9 studies were all from East Asian with 7 from mainland China [34][35][36][37][38][39][40], 1 from Korea [41] and 1 from Taiwan [42]. All these studies were single-center trials published from 2012 to 2018.…”
Section: The Characteristics and Quality Of The Included Studiesmentioning
confidence: 99%